2016
DOI: 10.1103/physrevlett.116.161102
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of Electrical Conductivity: A New Source for Astrophysical Magnetic Fields

Abstract: We consider the generation of magnetic field by the flow of a fluid for which the electrical conductivity is nonuniform. A new amplification mechanism is found which leads to dynamo action for flows much simpler than those considered so far. In particular, the fluctuations of the electrical conductivity provide a way to bypass anti-dynamo theorems. For astrophysical objects, we show through three-dimensional global numerical simulations that the temperature-driven fluctuations of the electrical conductivity ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Here, U and V represent the azimuthal and meridional velocity amplitude, respectively (in the case that + = U V 0, this is the same as Petrelis et al 2016). As discussed in Section3, the winds in the hot Jupiter atmosphere are largely two-dimensional and are reasonably described by (11).…”
Section: Analytic Models Of Dynamo Behavior In a Hot Jupitermentioning
confidence: 98%
See 1 more Smart Citation
“…Here, U and V represent the azimuthal and meridional velocity amplitude, respectively (in the case that + = U V 0, this is the same as Petrelis et al 2016). As discussed in Section3, the winds in the hot Jupiter atmosphere are largely two-dimensional and are reasonably described by (11).…”
Section: Analytic Models Of Dynamo Behavior In a Hot Jupitermentioning
confidence: 98%
“…This is to be contrasted with (4) in Petrelis et al (2016), where there is no spatial variation in η and a time derivative is included. We then write h h dh…”
Section: Analytic Models Of Dynamo Behavior In a Hot Jupitermentioning
confidence: 99%
“…For a linear dependence of σ on T, this would correspond to relative variations of σ of 3-7 %, making the dimensionless parameter δVL/η large enough for the α σ -effect to play a role. In Pétrélis et al (2016), it was suggested that ohmic dissipation might be another possible source for conductivity variations: if electrical currents produce sufficiently strong Joule heating, they could modify the local conductivity, suggesting a new scenario for a subcritical dynamo instability based on the α σ -effect.…”
Section: Mean-field Dynamos With Electrical Conductivity Gradientsmentioning
confidence: 99%
“…In other words, is a function of space and time , leading to the modified induction equation Because is now a function of space, the last term does not simply reduce to a diffusion term. Insight can be obtained using the approximation of scale separation (Pétrélis, Alexakis & Gissinger 2016). We assume that the velocity and conductivity fields are periodic of period .…”
Section: Mean-field Dynamos With Electrical Conductivity Gradientsmentioning
confidence: 99%
See 1 more Smart Citation